Splitting the Hedgehog signal: sex and patterning in Drosophila. - Horabin, J.I. (Development, 2005)
Sex-lethal (Sxl), the Drosophila sex-determination master switch, is on in females and controls sexual development as a splicing and translational regulator. Hedgehog (Hh) is a secreted protein that specifies cell fate during development. Previous work has demonstrated that Sxl protein is part of the Hh cytoplasmic signaling complex and that Hh promotes Sxl nuclear entry. In the wing disc anterior compartment, Patched (Ptc), the Hh receptor, acts positively in this process. Here, it is shown that the levels and rate of nuclear entry of full-length Cubitus interruptus (Ci), the Hh signaling target, are enhanced by Sxl. This effect requires the cholesterol but not palmitoyl modification on Hh, and expands the zone of full-length Ci expression. Expansion of Ci activation and its downstream targets, particularly decapentaplegic the Drosophila TGFbeta homolog, suggests a mechanism for generating different body sizes in the sexes; in Drosophila, females are larger and this difference is controlled by Sxl. Consistent with this proposal, discs expressing ectopic Sxl show an increase in growth. In keeping with the idea of the involvement of a signaling system, this growth effect by Sxl is not cell autonomous. These results have implications for all organisms that are sexually dimorphic and use Hh for patterning.